2019
DOI: 10.1016/j.jid.2019.03.620
|View full text |Cite
|
Sign up to set email alerts
|

544 Alopecia areata lesions show significant changes in immune and keratin biomarkers that correlate with clinical improvement with oral Janus kinase inhibitors PF-06651600 (JAK3) and PF-06700841 (TYK2/JAK1)

Abstract: Oral JAK3 (PF-06651600) and TYK2/JAK1 (PF-06700841) inhibitors were shown to be efficacious and well tolerated in patients with moderate to severe (50% scalp hair loss) alopecia areata (AA). A substudy of this Phase 2 trial (PF-06651600, n¼18; PF-06700841, n¼16; placebo, n¼12) evaluated changes in lesional scalp biomarkers after 12 and 24 weeks of treatment using microarrays, qPCR, and immunohistochemistry. A total of 2264 genes were significantly up-or downregulated after 12 or 24 weeks of treatment across al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 0 publications
1
4
0
Order By: Relevance
“…54 Our study supports the rationale for larger studies to explore JAK inhibition in FFA, particularly JAK3 inhibition that showed significant clinical benefits in several clinical trials in moderate-to-severe patients with AA. 41,42,[55][56][57] The most striking difference between AA and FFA molecular signatures was the lack of downregulation of hair keratins in FFA, in contrast with their consistent suppression in AA, as previously reported. 35,48 The keratins include early, middle and late keratinization genes, such as KRT86 and KRT83, which serve as AA treatment response biomarkers.…”
Section: Discussionsupporting
confidence: 69%
See 2 more Smart Citations
“…54 Our study supports the rationale for larger studies to explore JAK inhibition in FFA, particularly JAK3 inhibition that showed significant clinical benefits in several clinical trials in moderate-to-severe patients with AA. 41,42,[55][56][57] The most striking difference between AA and FFA molecular signatures was the lack of downregulation of hair keratins in FFA, in contrast with their consistent suppression in AA, as previously reported. 35,48 The keratins include early, middle and late keratinization genes, such as KRT86 and KRT83, which serve as AA treatment response biomarkers.…”
Section: Discussionsupporting
confidence: 69%
“…In sum, the diminished but still present stem cells in FFA lesions and largely unaffected stem cells in nonlesional FFA, together with the strong upregulation of T-cell activation/ Th1/JAK-STAT-related pathways and their correlation with fibrosis, along with recent therapeutic success of immunebased therapies in AA models and patients with moderate-tosevere AA, [39][40][41] provide hope for testing and development of targeted therapies for FFA. We acknowledge that our study was limited by the relatively small number of patients, and lack of global profiling with RNA-Seq.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The sample size was based on the primary efficacy outcome, that is, change in SALT score at week 24 in drug compared to placebo. For patients with similar disease severity, a change in SALT of less than 5 units was observed in placebo 23 . Assuming that at week 24 dupilumab will induce a change in SALT of at least 25 with a standard deviation of 10, a total sample size of 54 patients randomized 2:1 dupilumab to placebo will provide 97% power to detect differences compared to placebo, based on a two‐sided Student's t ‐test with a type I error α = 0.05.…”
Section: Methodsmentioning
confidence: 94%
“…For patients with similar disease severity, a change in SALT of less than 5 units was observed in placebo. 23 Assuming that at week 24 dupilumab will induce a change in SALT of at least 25 with a standard deviation of 10, a total sample size of 54 patients randomized 2:1 dupilumab to placebo will provide 97% power to detect differences compared to placebo, based on a two-sided Student's t-test with a type I error α = 0.05. Assuming a 10% dropout rate, the planned sample size was a total of 60 patients.…”
Section: Methodsmentioning
confidence: 99%